2012
DOI: 10.1371/journal.pone.0045532
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of the Teratoma Assay for Analysis of Pluripotency of Human ES Cells and Biosafety of Their Differentiated Progeny

Abstract: Teratoma tumor formation is an essential criterion in determining the pluripotency of human pluripotent stem cells. However, currently there is no consistent protocol for assessment of teratoma forming ability. Here we present detailed characterization of a teratoma assay that is based on subcutaneous co-transplantation of defined numbers of undifferentiated human embryonic stem cells (hESCs) with mitotically inactivated feeder cells and Matrigel into immunodeficient mice. The assay was highly reproducible and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 29 publications
1
96
3
Order By: Relevance
“…The teratoma formation experiments were performed as previously described [13] with subcutaneous implantation of *5 · 10 5 -1 · 10 6 cells into young (7 week old) severe combined immunodeficiency (SCID)-beige mice. Four animals were used per cell line (n = 4).…”
Section: Teratoma Formationmentioning
confidence: 99%
“…The teratoma formation experiments were performed as previously described [13] with subcutaneous implantation of *5 · 10 5 -1 · 10 6 cells into young (7 week old) severe combined immunodeficiency (SCID)-beige mice. Four animals were used per cell line (n = 4).…”
Section: Teratoma Formationmentioning
confidence: 99%
“…Low levels of aneuploidy in a diploid culture may be quite normal as this appears commonly in hESC and iPSC. Marti et al, 2013;Singh et al, 2012;Brivanlou et al, 2003;Gonzalez et al, 2011Andrews, 2002Draper et al, 2002;Henderson et al, 2002;Pera et al, 2000Sperger et al, 2003Richards et al, 2004Nazareth et al, 2013 Itskovitz-Eldor et al, 2000 Chambers et al, 2009;Borowiak et al, 2009;Burridge et al, 2012;Kattman et al, 2011Gertow et al, 2007Gropp et al, 2012Avior et al, 2015Muller et al, 2011Bock et al, 2011Cahan et al, 2014a ture, the quality of the passage method, and the split ratio. It is important to minimize the passage level of cells in routine use and to replace the in-use stock from a frozen cell bank on a regular basis.…”
Section: Whether Ipsc Recapitulate Esc Characteristics Exactly Is Stillmentioning
confidence: 99%
“…As mentioned above, teratoma formation assays are defined as the "golden standard" of pluripotency testing; however, this is not a standardized assay. Methods differ in cell preparation, cell numbers, the site of transplantation, the usage of Matrigel and the time of animal monitoring (Gropp et al 2012). These are essential factors, since it could be shown that teratoma formation depends on the site of injection and concomitant injection of Matrigel (Hentze et al 2009;Prokhorova et al 2009).…”
Section: Tumorigenicity Of Hesc and Hipscmentioning
confidence: 99%
“…This hallmark of pluripotency is a main challenge in the usage of hESC and hiPSC for clinical applications. It was shown that populations of differentiated cells contaminated with as few as 100 hESC cells are able to induce teratoma formation (Gropp et al 2012;Hentze et al 2009), and differentiation protocols are not completely effective (Hentze et al 2007). To overcome this problem, different strategies were reported, including activation of transfected "suicide genes," selection of specific cell types, hESC depletion with antibodies, small molecule inhibitor treatment and cytotoxic antibodies.…”
Section: Tumorigenicity Of Hesc and Hipscmentioning
confidence: 99%